Study of the longitudinal spin Seebeck effect in hybrid structures with yttrium iron garnet and various metallic materials - Guerra, Gabriel Andrés Fonseca (2014)
In this master thesis we study experimentally the longitudinal spin Seebeck effect (LSSE) in bilayers made of a ferromagnetic insulator (FMI) and a metallic layer (M). We also present a theoretical model based on the spin current density ⃗ Js carried by a non-equilibrium magnon distribution, generated by a thermal gradient ∇T across the thickness of the FMI. When ⃗ Js reach the FMI/M interface it is pumped towards the M layer due to conservation of the angular momentum, so, the M layer is essential for the LSSE existence. Here the FMI consists of a Yttrium Iron Garnet (YIG) lm, grown over a Gadolinium Gallium Garnet (GGG) substrate. Different metallic materials were used as the M layer i.e. Pt and Ta that have normal behavior and Py that is a ferromagnetic metal (FMM). The experimental procedure consists of systematic measurements of the electric voltage VISHE, produced by ⃗ Js through the Inverse Spin Hall Effect (ISHE) in the normal metal or (FMM) layer. In YIG/Pt measurements were done in the temperature range from 20 to 300 K. The experimental data are tted to the proposed model for the LSSE and good agreement is obtained. The results shows that the Py and Ta can be used to detect the LSSE with the ISHE. The results of this master thesis have strong interest in the area of spin caloritronics helping to the development of the eld and to raise possibilities of new spintronic devices. ----- Nesta diserta ção e estudado experimentalmente o Efeito Seebeck de Spin Longi- tudinal (LSSE), em bicamadas formadas por um isolante ferromagn etico (FMI) e um lme metalico (M). Tamb em foi desenvolvido um modelo te orico baseado na den- sidade de corrente de spin ⃗ Js que existe quando uma distribui c~ao de m agnons fora do equil brio e gerada por um gradiente t ermico ∇T aplicado na sec ção transversal do FMI. Quando ⃗ Js chega na interface FMI/M e bombeada para a camada M satis- fazendo a conserva ção do momentum angular, assim que a camada NM e essencial para ter um LSSE. Como camada FMI foi utilizada a granada de trio e ferro (YIG) crescida num substrato de (GGG). Diferentes materiais metalicos foram utilizados como camada M, sendo Pt e Ta paramagn eticos e o Py ferromagnetico. O proced- imento experimental consiste na medi c~ao sistem atica da voltagem el etrica VISHE, que e produzida por ⃗ Js por meio do efeito Hall de spin inverso (ISHE) que ocorre na camada M. As medidas em YIG/Pt foram feitas numa faixa ampla de temperatura de 20 a 300 K. Os dados experimentais são fi tados com a teoria proposta para o LSSE encontrando-se boa concordância. Nossos resultados mostram que o Py e o Ta s~ao bons candidatos para detec ção do LSSE. Esta disserta ção e de grande interesse na area da caloritrônica de spin, ajudando no desenvolvimento deste campo e na concep ção de novos dispositivos tecnol ogicos baseados na spintrônica.